MENEROPONG PEDOMAN AL-QUR'AN DAN HADIS TENTANG KOMPONEN KURIKULUM PENDIDIKAN - Thobroni, Ahmad Yusam; Faiqoh, Kholisotul; Havida, Nadhiva Iffany (Atta'dib Jurnal Pendidikan Agama Islam, 2024)
In educational activities, a comprehensive, structured, and integrated learning design framework is needed to be implemented so that the educational objectives can be achieved properly, where the design is called the educational curriculum. The existence of an educational curriculum is very important, because in addition to being the heart of education, the curriculum is also the main reference in the process of education. This research uses the library research method, using the maudhu'i interpretation presentation method through procedures; determining the theme, collecting verses and hadith about the education curriculum, classifying in sub-themes, analyzing the content and concluding the data. The results of the study state that the educational curriculum includes three important components namely linguistics, naqli science, and aqli science. Linguistics is the main means of obtaining knowledge, naqli science is science derived from the Qur'an and as-sunnah, and aqli science is science derived from human thought. With these three components the curriculum will form a balanced person kamil between religious knowledge and general knowledge through learning that is relevant to the times. Keywords: Looking at; Guidelines; Educational Curriculum Components; Al-Qur’an Hadis